Research methods for industrial and organizational psychology : science and practice - Landers, Richard N.; Behrend, Tara S. (New York, NY : Routledge, 2024)
"This important and useful book offers a clear and comprehensive foundation for research methods in industrial and organizational (IO) psychology. The text provides readers with a key understanding of the research, theory, and practise needed to become a research methods expert"--
Keywords: Psychology, Industrial -- Research -- Methodology; Organizational behavior -- Research -- Methodology; PSYCHOLOGY / General; PSYCHOLOGY / Industrial & Organizational Psychology